Computational study of thalamocortical interactions: simulating oscillatory activity - Shimoura, Renan Oliveira (2021)
The brain displays various oscillatory rhythms across scales that are related to one or multiple cognitive functions. One of the most prominent features in waking electroencephalograms of a variety of mammals, mainly observed at rest with eyes-closed, is the alpha rhythm (~ 10 Hz). Although alpha is strongly associated with reduced visual attention, it is also related to other roles. Understanding how and where this rhythm is generated can elucidate its functions. Even today there is no definitive answer to this question, though several hypotheses put forward the thalamus and the cortex as possible protagonists. This work aims to explore possible alpha generators in a multilayered microcircuit model of the primary visual cortex connected to a thalamic network. The spontaneous activity of the cortical microcircuit was analyzed and two hypotheses of the generation of alpha were studied. We showed that alpha oscillations emerge by adding intrinsically bursting neurons at cortical layer 5 and by changing the thalamocortical loop delay. These hypotheses pointed to generators from different sources, one pointing layers 5 and 2/3 and the other pointing layers 4 and 6, and they are comparable with experimental works.